PENERAPAN TRANSPARANSI DAN AKUNTABILITAS DALAM PENGELOLAAN KEUANGAN BADAN KESWADAYAAN MASYARAKAT (BKM) DI LOKASI EKS PROGRAM PNPM MANDIRI PERKOTAAN(Studi kasus di Desa Montong Are Lombok Barat Tahun 2019) - Fathurrahman, Fathurrahman (Nusantara Hasana Journal, 2021)
This study aimed to determine the process of transparency and accountability in the financial management of the BKM at Montong Are Urban Village West Lombok. The method used in this research is using qualitative methods. Qualitative method is a method of research used to examine the condition of natural objects, in which the researcher is a key instrument, data collection techniques are combined, data analysis is inductive, and qualitative research results further emphasize the significance of the generalization. The conclusion of this study is BKM Lestari Montong Are capable of running the Transparency and Accountability in good financial management.